Ecological Studies on Hippophae Rhamnoides Linn. In Spiti Valley of Himachal Pradesh - Singh, R P; Bahar, Nawa; Prasad, Bhagwati; Gupta, M K (Annals of Arid Zone, 2016)
The study was conducted in the cold desert of Spiti Valley in the state ofHimachal Pradesh. Plantation of Hippophae rl1amnordes Linn in one hectareÂ area can meet the fuelwood needs of twenty families in this region. TotalÂ biomass dry weight basis was 34.27 t/ha and energy ranged from 3.5 to 4.4 K.cal/g dry weight.